2017
DOI: 10.1093/jrr/rrx052
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response curves for analyzing of dicentric chromosomes and chromosome translocations following doses of 1000 mGy or less, based on irradiated peripheral blood samples from five healthy individuals

Abstract: In terms of biological dosimetry at the time of radiation exposure, the dicentric chromosome (Dic) assay (DCA) is the gold standard for assessing for the acute phase and chromosome translocation (Tr) analysis is the gold standard for assessing the chronic phase. It is desirable to have individual dose–response curves (DRCs) for each laboratory because the analysis criteria differ between laboratories. We constructed the DRCs for radiation dose estimation (with three methods) using peripheral blood (PB) samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
14
2
Order By: Relevance
“…In our study, type E acentric fragments increased by a factor of 2.9 after 20 MRI sessions, equivalent to their tripling, very low in comparison with CT scans. Moreover, and interestingly, the profile of CA evolution in MRI-exposed volunteers was not the same as those usually observed after CT scans [22][23][24][25][26][27], as we mainly detected chromosomal deletions and no increase in Dics, the hallmark of irradiation. We hypothesise that the number of DSBs induced per cell by repeated MRIs is too low to induce chromosomal fusion.…”
Section: Discussioncontrasting
confidence: 52%
“…In our study, type E acentric fragments increased by a factor of 2.9 after 20 MRI sessions, equivalent to their tripling, very low in comparison with CT scans. Moreover, and interestingly, the profile of CA evolution in MRI-exposed volunteers was not the same as those usually observed after CT scans [22][23][24][25][26][27], as we mainly detected chromosomal deletions and no increase in Dics, the hallmark of irradiation. We hypothesise that the number of DSBs induced per cell by repeated MRIs is too low to induce chromosomal fusion.…”
Section: Discussioncontrasting
confidence: 52%
“…It is also important to record that dicentric aberrations are hardly induced by low radiation doses thus putting an additional constraint on the popular DCA method [38][39][40][41]. The di culty in estimating dose-response curves for low dose range was expressed and was concluded that DCA as well as translocation analysis after gamma irradiation particularly less than a 0.1 or 0.05 Gy was devoid of accuracy and showed poor dose-response [42]. However, accuracy could be improved by analyzing more than 5000 cells for the low dose range [43], which might be impractical in case of a radiation disaster situation.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently stable complex exchanges (3 or more breaks in 2 or more chromosomes) were broken down into simple translocations and included in the total translocation count [19,20]. Genomic frequencies of stable chromosomal translocations (F G ) were calculated according to a standard formula proposed by Lucas and Sachs [21].…”
Section: Subjects (Participants)mentioning
confidence: 99%